The Mosque Typology of Aceh’s Northern-Eastern Region, Indonesia - Fakriah, Nurul; Bakri, Maysarah (Journal of Islamic Architecture, 2025)
This study is an extended research of previous studies on the mosque typology in Aceh Province, Indonesia. Although Aceh is well-known as a “mecca veranda” due to its proximity to Islam, the mosque typology research is still limited. The mosque holds significant value in the Muslim community. This study was conducted in Aceh’s Northern-Eastern route, which covers 90 (ninety) mosques located in 8 (eight) regencies. Using Baiturrahman Grand Mosque as the reference, as suggested in previous studies, the result indicates that the union-shaped mosque as a roof element is the predominant feature replicated by the mosques in Aceh’s Northern-Eastern route. Other elements, such as the column, the opening, and the roof ornamentation, are also replicated by some research objects insignificantly. Differing from the previous research, this study highlights that the minaret is a vital feature, although it is not applied in all research objects. Further research can be carried on toward broader areas with more diverse analytical factors such as time, socio-culture and technology.